KETERAMPILAN KEPEMIMPINAN KEPALA MADRASAH DALAM PENGELOLAAN GURU DAN KARYAWAN (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2020)
This article is aimed to describe school principals’ leadership skill in managing teachers and employees. To manage teachers and employees, school principals are in need of leadership skill to manage, coordinate, and encourage them to have active role, become creative, innovative, and productive in improving education quality. The study is performed as a library research adopting qualitative approach and descriptive method. Data analysis is run through interrelated processes of data collection, data processing, and data analysis. Result of study indicated that to become a successful school principal in managing teachers and employees, it requires: 1) skill to organize and encourage teachers and employees, 2) skill to nourish teachers and employees’ self-confidence, 3) skill to improve teachers and employees professionalism, 4) skill to build a solid and strong team work, and 5) skill to drive teachers and employees to achieve school goals.